Supervisi Pendidikan Persfektif Islam - Nuraini (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The aim of educational supervision is to provide technical assistance and guidance to teachers and other school staff so that these personnel are able to improve the quality of their performance, especially in carrying out tasks, namely carrying out the learning process. Furthermore, if the quality of the performance of teachers and staff has increased. educational supervision provides assistance in the form of continuous guidance both individually and in groups in improving learning so as to improve the quality of the school as a whole. Controlling or supervision in Arabic has the same meaning as the word ar-Riqobah. In the Qur'an, this word is mentioned in several verses which generally indicate the existence of a supervisory function. Ar-riqobah is knowing the actual events with the rules and regulations, as well as pointing precisely to the bases that have been set in the original planning. In this context, sharia implementation is realized through three pillars of supervision, namely: 1) individual piety, that all company personnel are ensured and nurtured to become pious human beings; 2) supervision of members, in an organizational atmosphere that reflects a team, the organization's sustainability process will always receive supervision from its personnel in accordance with the direction that has been set; 3) Implementation/supremacy of rules, organizations are upheld by clear and transparent rules of the game and are not against sharia.